2018
DOI: 10.4103/1735-5362.220969
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate protects the heart against carbon monoxide-induced cardiotoxicity in rats

Abstract: Carbon monoxide (CO), a toxic gas produced via incomplete fossil fuel combustion, has several poisonous effects in the heart including induction of necrosis, apoptosis, and electrocardiogram (ECG) changes. Magnesium sulfate (MS) is a drug with cardioprotective effects especially when used after ischemia/reperfusion. In the current study, we aimed to evaluate MS cardioprotective effects following CO poisoning. Animals were exposed to CO 3000 ppm for 1 h and immediately after the exposure period and on the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the current study, we demonstrated that MS decreased brain cell necrosis, apoptosis and oxidative stress, while it increased pro-survival Akt protein levels in a dose-dependent manner. Previously, we reported several neuroprotective and cardioprotective substances, which may be used to decrease CO poisoning consequences, in animal models (2,33,36,37,42,4446). More specifically, in a recent study from our group, MS administration was found to exert positive effects against the cardiotoxicity of CO in rats (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrated that MS decreased brain cell necrosis, apoptosis and oxidative stress, while it increased pro-survival Akt protein levels in a dose-dependent manner. Previously, we reported several neuroprotective and cardioprotective substances, which may be used to decrease CO poisoning consequences, in animal models (2,33,36,37,42,4446). More specifically, in a recent study from our group, MS administration was found to exert positive effects against the cardiotoxicity of CO in rats (33).…”
Section: Discussionmentioning
confidence: 99%